Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1053/j.gastro.2012.06.043
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Administered Redox Nanoparticle That Accumulates in the Colonic Mucosa and Reduces Colitis in Mice

Abstract: We designed an orally administered RNP(O) that accumulates specifically in the colons of mice with colitis and is more effective in reducing inflammation than low-molecular-weight TEMPOL or mesalamine. RNP(O) might be developed for treatment of patients with ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(128 citation statements)
references
References 38 publications
5
123
0
Order By: Relevance
“…Furthermore, these 40 nm particles prevent the uptake into bloodstream via mesentery. Along with these characteristics, we have confirmed that RNP O effectively scavenges ROS to result in significant suppression of inflammation in mice with colitis [21]. Suppression of inflammation in the tumor microenvironments is reported to work as suppressor of tumor progression and resistance against chemotherapy [23].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, these 40 nm particles prevent the uptake into bloodstream via mesentery. Along with these characteristics, we have confirmed that RNP O effectively scavenges ROS to result in significant suppression of inflammation in mice with colitis [21]. Suppression of inflammation in the tumor microenvironments is reported to work as suppressor of tumor progression and resistance against chemotherapy [23].…”
Section: Introductionsupporting
confidence: 58%
“…RNP O was prepared by a self-assembling MeO-PEG-b-PMOT block copolymer, as previously reported [21,25]. Briefly, methoxy-poly(ethylene glycol)-b-poly(-chloromethylstyrene) (MeO-PEG-b-PCMS) was synthesized by the radical telomerization of chloromethylstyrene (CMS; Seimi Chemical Co., Ltd., Kanagawa, Japan) using methoxy-poly(ethylene glycol)-sulphanyl (MeO-PEG-SH; NOF Corporation Co., Ltd., Tokyo, Japan; Mn ¼ 5000) as a telogen (the degree of polymerization of CMS ¼ 16 units).…”
Section: Preparation Of Rnp Omentioning
confidence: 99%
See 1 more Smart Citation
“…Within the damaged epithelium, neutrophils and macrophages are the most common immune cells present. Therapies that target the downstream mediators of these cells, such as reactive oxygen species, are therefore protective (Krieglstein et al 2001;Amrouche-Mekkioui and Djerdjouri 2012;Vong et al 2012;Yasukawa et al 2012). While the acute chemical-induced colitis models typically only incorporate features of innate biology (both epithelial and immune), the chronic and progressive models typically illustrate a complex interplay between innate biology and adaptive immune responses.…”
Section: Considerations For Choosing a Preclinical Modelmentioning
confidence: 99%
“…For example, a novel redox nanoparticle (RNP O ) consisting of a self-assembling ampiphilic block copolymer containing a derivative of the antioxidant TEMPOL (4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl) in the hydrophobic segment has been shown to be more effective than free TEMPOL or mesalamine (an anti-inflammatory compound) at treating colitis in mice (190).The confinement of the nitroxide radical-containing TEMPOL derivative in the hydrophobic core of RNP O nanoparticles enhanced its biocompatibility, and the nanoparticles' size (40 nm) caused them to accumulate in the colonic mucosa. A recent report described the antioxidant properties of nanoparticles (PVAX) formulated from copolyoxylate containing vanillyl alcohol (VA) (110).…”
Section: Challenges In Evaluating In Vivo Applicabilitymentioning
confidence: 99%